The frequency of using different types of pacifier and bottle nipple among 1-24 months old‎ children - Hamidreza Poureslami (Journal of Oral Health and Oral Epidemiology, 2015)
BACKGROUND AND AIM: Sucking of some types of a pacifier may be a risk factor for mal-development of orofacial structures and malocclusion. This study assessed the prevalence of using of different types of pacifier and bottle nipple among 1-24 months old children in Kerman, Iran.